(untitled) (Research, Society and Development, 2022)
Down syndrome, or Trisomy 21, is a genetic abnormality characterized by deficiencies such as delayed mental and physical development. It affects craniofacial growth, becoming an important factor in altering the stomatognathic system, resulting in specific oral characteristics such as class III malocclusion, which may compromise the performance of vital functions related to quality of life such as chewing, communication, swallowing and complications respiratory. The study aimed to expose the orthognathic surgical modalities used to correct Angle class III malocclusion in a patient with DS, in order to allow the patient with DS an improvement in the performance of oral functions. Articles published between 2019 and 2022 were used in the following databases: Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS) and Virtual Health Library (BVS). The study resulted in bimaxillary surgery, mandibular setback surgery, and maxillary advancement surgery. With this, the study concludes that orthognathic surgery to correct Angle class III malocclusion in individuals with Down syndrome is considered a form of treatment for the dentofacial deformities of these patients, enabling them to improve their quality of life, a improvement in the quality of performance of orofacial functions and better social, cultural and individual development.